Ideal Leadership Profile in Resolving Conflict in Schools - Achfama, Durarin Nuha; Pratiwi, Cerianing Putri; Listiani, Ivayuni (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Conflicts that occur in the school environment are not necessarily an indication of the death of an organization. In fact, conflict can be a catalyst for improvement if principals and school communities collaborate to find solutions. In overcoming conflicts, school principals must have the competencies needed for a leader as specified in the Regulation of the Ministry of Education and Culture in 2007. This research aims to identify the core competencies that school principals must have in order to effectively manage and resolve conflicts in schools. This research is a descriptive research of literature. The four general stages in literature research are (1) collecting notes that are in accordance with the topic, (2) integrating relevant theories as a process of integrating concepts found in the literature being studied, (3) analyzing the advantages and disadvantages of each source used, and (4) conducting an analysis and analysis of the scientific arguments from the results. The study reveals that several key elements contribute to the principal's ability to handle conflict effectively, including: (1) strong communication skills that include interpersonal, group, and organizational communication; (2) managerial ability in determining the priority of steps and processes; and (3) democratic leadership.